The effects of perception of video image and online word of mouth on tourists’ travel intentions: Based on the behaviors of short video platform users - Zhou, Yang; Liu, Ligang; Sun, Xiao (Frontiers in Psychology, 2022)
This research, based on the theory of emotional evaluation, discusses how the perception of video images impacts on tourists’ intention to visit these destinations. A survey of 390 users of short video platforms has been conducted, on the basis of structural equation model. The results are as follows. First, the perception of video images can significantly affect tourists’ intention to visit these places. Second, online word of mouth, as a mediating variable, can enhance the positive effects of the perception of video images on tourists’ travel inclinations. Third, the positive moderating effect of gender can be particularly obvious in the relationship between the perception of video images and online word of mouth. This research provides a theoretical basis for the utility of tourism-related short videos, which can help stimulate tourists’ intention to visit promoted destinations.